2022
DOI: 10.11648/j.ab.20221001.13
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Varied Inflammatory Indices in the Prediction of COVID-19 Severity Among Nigerians

Abstract: Background: The coronavirus disease of 2019 ) is theorized to be associated with significant inflammatory episodes. This tends to define the severity and culminates in adverse consequences of the disease. Therefore, the current study evaluated the potentials of varied inflammatory markers/indices that define the COVID-19 severity. Methods: This was a retrospective analysis of pre-treatment data obtained from patients with positive real-time polymerase chain reaction (RT-PCR)-confirmed COVID-19 disease in one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Data also indicate that the hepatocellular-specific pattern of liver pathologies occurs early during SARS-CoV-2 infection which transitions to the cholestatic-specific pattern with worsening severity of the infection [25]. As previously documented, worsening COVID-19 severity is associated with marked hyper-inflammatory responses [12]- [15]. This may also explain the correlation documented between inflammatory markers and those of cholestatic-specific markers in the current study.…”
Section: Pathomechanismssupporting
confidence: 86%
See 1 more Smart Citation
“…Data also indicate that the hepatocellular-specific pattern of liver pathologies occurs early during SARS-CoV-2 infection which transitions to the cholestatic-specific pattern with worsening severity of the infection [25]. As previously documented, worsening COVID-19 severity is associated with marked hyper-inflammatory responses [12]- [15]. This may also explain the correlation documented between inflammatory markers and those of cholestatic-specific markers in the current study.…”
Section: Pathomechanismssupporting
confidence: 86%
“…The mechanism underlying the COVID-19-induced hepatobiliary pathologies is conflicting in the literature, though several investigators have suggested the involvement of the hyper-inflammatory response [6]- [11]. Hyperinflammatory response is a cardinal feature of disease [12]- [15]. However, a large number of the previous studies on this subject have been documented among western populations while including patients with various pre-existing comorbid conditions and those on various medications/toxicants known to have negative influence on normal hepatobiliary functions [6]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various studies have been documented on the hyper-inflammatory responses to COVID-19 [20]- [23]. Consequently, COVID-19-induced dyslipidemia has been implicated in the tendency to develop hyper-inflammatory responses among patients with the disease.…”
Section: B Relationship With Existing Literaturementioning
confidence: 99%
“…SARS-CoV-2 can infect and damage various tissues in the body, including the oesophageal epithelial cells, type II alveolar cells, renal proximal tubule cells, and myocardial cells. [ 2 ] Those tissues contain angiotensin-converting enzyme-2 (ACE2) receptors, which make them vulnerable to infection. As a result, serologic indicators of inflammation, such as interleukin-6 (IL-6), C-reactive protein (CRP), lactate dehydrogenase (LDH), D-dimer, ferritin, and procalcitonin, have been increased.…”
Section: Introductionmentioning
confidence: 99%